2020
DOI: 10.1038/s41419-020-2502-4
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosome-dependent myotube formation involves activation of caspase-3 in differentiating myoblasts

Abstract: Caspase-2, -9, and -3 are reported to control myoblast differentiation into myotubes. This had been previously explained by phosphatidylserine exposure on apoptotic myoblasts inducing differentiation in neighboring cells. Here we show for the first time that caspase-3 is activated in the myoblasts undergoing differentiation. Using RNAi, we also demonstrate that differentiation requires both cytochrome c and Apaf-1, and by using a new pharmacological approach, we show that apoptosome formation is required. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Apaf-1 levels are also decreased in some cancers by microRNAs. Notably one miRNA that targets Apaf-1, miR-221, is increased during neuronal differentiation ( Hamada et al, 2012 ) and during myogenesis ( Liu et al, 2018 ), both systems where a decrease in Apaf-1 level appears to be important step during differentiation ( Fernando et al, 2005 ; Dehkordi et al, 2020 ). Other microRNAs are reported to regulate Apaf-1 in cancers, but their roles in neurogenesis and myogenesis are not well described.…”
Section: Controlling Apoptotic Caspases During Non-apoptotic Processesmentioning
confidence: 99%
“…Apaf-1 levels are also decreased in some cancers by microRNAs. Notably one miRNA that targets Apaf-1, miR-221, is increased during neuronal differentiation ( Hamada et al, 2012 ) and during myogenesis ( Liu et al, 2018 ), both systems where a decrease in Apaf-1 level appears to be important step during differentiation ( Fernando et al, 2005 ; Dehkordi et al, 2020 ). Other microRNAs are reported to regulate Apaf-1 in cancers, but their roles in neurogenesis and myogenesis are not well described.…”
Section: Controlling Apoptotic Caspases During Non-apoptotic Processesmentioning
confidence: 99%
“…Bax counteracts the effect of Bcl-2, which induces cytochrome c release to cytosol. When cytochrome c flows to the cytosol, it results in the establishment of apoptosome and the following caspase activation [21]. Our results revealed that the treatment with TMZ alone increased the Bcl-2 expression, suggesting the drug-resistant effect of TMZ on U87MG glioma cells.…”
Section: Discussionmentioning
confidence: 59%
“…These results indicate that not only caspases but the entire apoptotic pathway can be activated to implement non-apoptotic functions. Importantly, this is not exclusive of our Drosophila cellular model since a similar requirement has recently been demonstrated during the differentiation of mammalian muscle precursors 51 .…”
Section: Discussionmentioning
confidence: 65%